SISTEM PENJAMINAN MUTU INTERNAL MADRASAH ANTARA TEORI DAN PRAKTIK - Muhyar Fanani (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
This paper discusses the application of internal quality assurance system in the madrasah (Islamic School). This paper concludes that the quality assurance system is a systematic effort to improve the quality of education in a sustainable cycle that is manifested in the form of quality assurance activities to prevent unnecessary mistakes. Quality assurance system has some of the principles underlying the system works. Those Principles are a). Identify customers and their needs. b). Creating quality measurements. c). Plan process to achieve goals. d). The existence of a continuous of progress. In order to create continuous improvement, the head of madrasah (Islamic School) need to apply Deming's wheel consisting of plan, do, check, and act. For those madrasah which has many limitations, the PDCA is run by following the advice of Joseph Juran, namely: First, run a Kaizen, ie step by step improvement. Second, choose a low-cost measures. A good plan should be drawn off from the vision and mission of the madrasah which then are translated into a quality policy and objectives (targets) while considering the quality of customer needs. From the quality objectives specified performance indicators so as to facilitate evaluation. When the indicator has not been as planned, it means that there must be a record of improvement. PDCA cycle never ends, because the continuous improvement should be always sought.